Study on the reconstruction method of stereo vision in glass flume. (April 2016) - Du, Hai; Li, Mu-guo; Meng, Juan
Highlights: A new 3D reconstruction method with refraction revision is proposed for the experiments in glass flume. The revision process for refraction distortion only need to know few parameters and no additional equipment is required. In the proposed method, the camera calibration need not be operated in water and this method is simple to apply. Abstract: In three-dimensional reconstruction experiments based on stereo vision theory in a glass flume, there is usually more than one medium in the travel path of the light, such as air, glass and water. These media not only degrade image quality, but also change the light route. Large errors are generated if the effects of these media are ignored. To solve the problems of media effects, a new method of object reconstruction for the glass flume is proposed, based on computer vision theory and laws of refraction. Firstly, the light refraction effects are analyzed and a coordinate correction formula is developed. Secondly, correction parameters are obtained based on a stereo vision method to correct the coordinates of a target point. Finally, model experiments in glass flume are described and the errors are analyzed. The experimental results show that the proposed method is effective in correcting refraction distortion, and improves the accuracy of three-dimensional reconstruction of target points.